1997
DOI: 10.1097/00003643-199707000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Antiseptic-impregnated central venous catheters reduce the incidence of bacterial colonization and associated infection in immunocompromised transplant patients

Abstract: P<0.002), a 68% reduction. Similarly, the incidence of concomitant infection, by the same organism at The incidence of bacterial colonization of central venanother site was reduced from 10 of 35 standard ous catheters using a standard polyurethane catheter catheters to 4 of 44 study catheters (P<0.03), a 63% was compared with that using an antiseptic (silver reduction. sulphadiazine and chlorhexidine) impregnated catheter in a group of patients with thoracic organ trans-Keywords: central venous catheters, infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…30,46,81,83 Six studies have compared the use of Groshong catheters with the use of Hickman catheters. In 4 of these studies, 1 randomized 84 and 3 nonrandomized, [85][86][87] no significant difference was found between the 2 catheters with regard to incidence of mechanical complications, 86 thrombosis, 84,87 or catheter-related infections. 84 -87 However, 2 prospective, randomized, controlled trials revealed that Hickman catheters had a lower incidence of catheter occlusion compared with the Groshong catheter.…”
Section: Tunneled Central Venous Cathetersmentioning
confidence: 97%
“…30,46,81,83 Six studies have compared the use of Groshong catheters with the use of Hickman catheters. In 4 of these studies, 1 randomized 84 and 3 nonrandomized, [85][86][87] no significant difference was found between the 2 catheters with regard to incidence of mechanical complications, 86 thrombosis, 84,87 or catheter-related infections. 84 -87 However, 2 prospective, randomized, controlled trials revealed that Hickman catheters had a lower incidence of catheter occlusion compared with the Groshong catheter.…”
Section: Tunneled Central Venous Cathetersmentioning
confidence: 97%
“…Excluded reference(s) Data on rate of colonization per 1000 catheter-days was not present [11][12][13][14][15][16][17][18][19] Data on rate of colonization per 1000 catheter-days was not present and catheter-tip culture method was not defined [20] Data on rate of colonization per 1000 catheter-days was not present and catheter-related BSI was treated without catheter removal [21] No data on catheter-related BSI [2,[22][23][24][25][26][27] Cutoff 1100 cfu/catheter tip (vs. 1000 cfu/catheter tip) [28] Catheter-tip culture method not defined [29] Other cutoffs for catheter culture used [14,30] Data for CVCs not separated from data for all catheters [31] NOTE. Catheter-related BSI is defined as a catheter-tip culture that yielded the same phenotypic strain as у1 culture of a blood sample obtained before catheter removal.…”
Section: Reason For Exclusionmentioning
confidence: 99%
“…This fi rstgeneration CHSS catheter is coated only on the exterior surface and exhibits antimicrobial properties for ~15 days. Since its introduction >8 million catheters have been sold worldwide and a considerable number of randomized clinical trials have been performed with this type of catheter (Sheng et al 2000 ;Hannan et al 1999 ;Collin 1999 ;Heard et al 1998 ;George et al 1997 ;Logghe et al 1997 ;Maki et al 1997 ;Tennenberg et al 1997 ;Bach et al 1996 ;Ciresi et al 1996 ;Pemberton et al 1996 ). In the study with the greatest patient numbers, which also used molecular methods for the confi rmation of CRBSI, the CHSS catheter was associated with a 2-fold reduction in the incidence of catheter colonisation and a 5-fold reduction of CRBSI (RR 0.21, 95 % CI 0.03, 0.95; p = 0.03) (Maki et al 1997 ).…”
Section: Antiseptics-containing Polymeric Catheter Materialsmentioning
confidence: 99%